Angiogenesis after acute myocardial infarction: a bibliometric -based literature review - Tan, Yu; Li, Min; Ma, Xiaojuan; Shi, Dazhuo; Liu, Wei (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveThe prevalence of acute myocardial infarction, a severe ischemic cardiac disease, is on the rise annually. The establishment of coronary collateral circulation in the border zone of the infarct can effectively relieve myocardial ischemia and impede cell death, while angiogenesis can promote the formation of collateral circulation in the ischemic tissues. Over the past two decades, studies related to angiogenesis in acute myocardial infarction have increased rapidly. However, there is a lack of bibliometric studies in this particular field.MethodsFor this study, we employed bibliometric analysis to outline focal points and patterns in scientific and clinical research. The collection of literature was gathered using the Web of Science Core Collection database. Bibliometric and visual analysis were conducted. Knowledge maps were generated using CiteSpace and VOSviewer software.Results and conclusionsWith the deepening of the research, therapeutic angiogenesis will become a treatment direction for acute myocardial infarction in the future.